Environmental smoking and smoking onset in adolescence: the role of dopamine-related genes. Findings from two longitudinal studies. - Marieke Hiemstra; Marloes Kleinjan; Onno C P van Schayck; Rutger C M E Engels; Roy Otten (PLoS ONE)
Although environmental smoking (i.e., paternal and maternal smoking, sibling smoking, and peer smoking) is one of the most important factors for explaining adolescent smoking behavior, not all adolescents are similarly affected. The extent to which individuals are vulnerable to smoking in their environment might depend on genetic factors. The aim of this study was to examine the interplay between environmental smoking and genes encoding components of the dopaminergic system (i.e., dopamine receptor D2, D4, and dopamine transporter DAT1) in adolescent smoking onset. Data from two longitudinal studies were used. Study 1 consisted of 991 non-smoking early adolescents (mean age = 12.52, SD = .57) whereas study 2 consisted of 365 non-smoking middle to late adolescents (mean age = 14.16, SD = 1.07) who were followed for 16 and 48 months, respectively. Logistic regression analyses were conducted using Mplus. In study 1, we found positive associations between parents' and friends' smoking at the first measurement and smoking status 16 months later. In study 2 we found a positive association between friends' smoking and smoking onset 48 months later. Neither study demonstrated any interaction effects of the DRD2, DRD4, or DAT1 genotypes. In conclusion, the effects of environmental smoking on smoking onset are similar for adolescent carriers and non-carriers of these specific genes related to the dopaminergic system.